Organosilicate polymer e‐beam resists with high resolution, sensitivity and stability. (31st October 2013) - Lee, Sung‐Il; Sim, Jae Hwan; Lee, Hae‐Jeong; Kasica, Richard; Kim, Hyun‐Mi; Soles, Christopher L.; Kim, Ki‐Bum; Yoon, Do Y.; Laine, Richard M.
<x xml:space="preserve">Abstract</x> Hydrogen silsesquioxane (HSQ) is an attractive electron‐beam (e‐beam) resist for sub‐20 nm lithography owing to its high resolution, excellent line‐edge roughness (LER) and good plasma etch resistance. However, the sensitivity and long‐term stability of HSQ need to be significantly improved to have HSQ resists adopted for volume manufacturing. Here we develop novel organosilicate e‐beam resists with improved e‐beam sensitivity and stability as an alternative to HSQ resists. Copolymers of norbornene ethyltrimethoxysilane (NETMS) with 1, 2‐bis(triethoxysilyl)ethane, synthesized via acid‐catalyzed sol–gel reactions, show excellent e‐beam sensitivity with around a sixfold reduction in the critical dose as compared with HSQ but poor LER characteristics. Terpolymers were then synthesized using p‐chloromethylphenyl trimethoxysilane (p‐CMPTMS), NETMS and tetraethoxysilane, which exhibit significant improvement in sensitivity as compared with previously reported materials, together with high‐resolution patterns and long‐term stability. High‐resolution patterns of features as small as 20 nm with excellent LER were successfully fabricated employing organosilicate terpolymers using a 100 keV e‐beam. The dose for patterning 20 nm lines was reduced from 4000 μC cm−2 for HSQ to 900 μC cm−2 for an optimized terpolymer resist. FT‐IR measurements suggest that the main reason for the increased e‐beam sensitivity is chain transfer reaction between the norbornene moieties, which provide an efficient cross‐linking mechanism by the e‐beam generated radicals. Copyright © 2013 John Wiley & Sons, Ltd.